(untitled) (The Review of Diabetic Studies, 2025)
Pulmonary arrest is one of the most life-threatening emergencies encountered in pre-hospital settings, with survival outcomes highly dependent on the speed, accuracy, and effectiveness of interventions performed by paramedics. As the first responders, paramedics play a pivotal role in reducing mortality through rapid assessment, airway management, ventilation support, high-quality cardiopulmonary resuscitation (CPR), defibrillation when indicated, and the timely administration of pharmacological agents. Recent advances in emergency medical services (EMS), including the integration of mechanical CPR devices, supraglottic airways, capnography, and telemedicine, have further expanded paramedics’ capacity to manage pulmonary arrest. However, significant challenges remain, including variability in training, differences in protocols, limited access to advanced technologies, and systemic delays in emergency activation and response times. This review synthesizes current evidence on strategies employed by paramedics to reduce mortality in pulmonary arrest cases, examining clinical, technological, and organizational approaches. Emphasis is placed on evidence-based practices, barriers to implementation, and strategies to strengthen paramedics’ effectiveness, including continuous education, standardized protocols, and innovative decision-support systems. By identifying best practices and highlighting gaps in the literature, this review aims to provide a comprehensive framework for optimizing pre-hospital care and improving survival rates in pulmonary arrest emergencies.